Facile preparation of hierarchical nanostructured CuInS2 counter electrodes for dye-sensitized solar cells. (30th November 2017) - Ravi Dhas, C; Christy, A Jennifer; Venkatesh, R; Monica, S Esther Santhoshi; Panda, Subhendu K; Subramanian, B; Ravichandran, K; Sudhagar, P; Raj, A Moses Ezhil
Abstract: CuInS2 (CIS) thin films have been synthesized onto the glass substrates for different solvent volumes (10, 30, 50 and 70 ml) by nebulizer spray technique. The effect of solvent volume on the structural, morphological, compositional, optical and electrical properties of CIS thin films has been investigated. X-ray diffraction patterns suggest that the obtained CIS films are polycrystalline with the tetragonal structure. The surface morphology of the prepared CIS films purely depends on the solvent volume. The elemental quantitative investigation and the stoichiometric ratio of the CIS thin films were verified from XPS and EDS. High absorbance with the optical band gap of 1.13 eV was obtained at the higher solvent volume. All the deposited CIS thin films exhibited p-type semiconducting behavior with the high electrical conductivity and carrier concentration. CIS thin films deposited onto the FTO substrate were used as a counter electrode (CE) in dye-sensitized solar cells. CIS CEs possessed high electrocatalytic behavior and fast electron charge transfer at the CE/electrolyte interface. The CIS CE prepared using 50 ml solvent volume generated high energy conversion efficiency of about 3.25%.